The Practice of Buying and Selling During Friday Prayer in Mandailing District Natal: A Study With A Maqashid Al-Syari'ah Approach - Hamid, Asrul; Putra, Dedisyah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
Islam, as a complete religion, regulates all human life. It regulates vertical ritual worship to Allah Almighty and regulates horizontal worship, namely the relationship between humans, so balance is needed in life. Humans as social creatures created by Allah need each other and cannot be separated from muamalah affairs such as buying and selling to fulfill their needs. Buying and selling is also a daily activity for everyone to meet the needs of their lives. Everyone who does buying and selling must know the law of buying and selling so that no one is harmed, especially the practice of buying and selling when Friday prayer are performed. Thus, the practice works under the provisions of Islamic law. Hablum minannas in the practice of muamalah towards fellow human beings must be in line with hablum minallah based on the guidance of Islamic law. Broadly speaking, Islamic law itself is divided into two; worship and muamalah. Muamalah is the rules (laws) of Allah Swt, intended to regulate human life in worldly affairs of a social nature. In this discussion, the author will explain the law of buying and selling during Friday prayer in Mandailing Natal Regency: a study with a maqashid al-syari'ah approach. This research is descriptive-analytical with the field study research through a normative, empirical approach. The results of this study is that the law of buying and selling that reaches the degree of urgency during Friday prayer is permissible with the aim of more significant benefit, namely protecting the soul (hifdzun an-Nafs) and (hifdzun al-Aql). This law applies in buying and selling medical drugs at pharmacies, hospitals, and other vital objects.